2023
DOI: 10.1101/2023.10.24.563810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic identification of cargo-carrying genetic elements reveals new dimensions of eukaryotic diversity

Emile Gluck-Thaler,
Aaron A. Vogan

Abstract: Cargo-carrying mobile elements (CCEs) are genetic entities that transpose diverse protein coding sequences. Although common in bacteria, we know little about the biology of eukaryotic CCEs because no appropriate tools exist for their annotation. For example, Starships are fungal CCEs whose functions are largely unknown because they require time-intensive manual curation. To address this knowledge gap, we developed starfish, a computational workflow for high-throughput eukaryotic CCE annotation. We applied star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…All nine Gaeumannomyces strains were found to contain at least one giant TE belonging to the Starship superfamily of giant cargo-carrying TEs (Gluck-Thaler et al 2022), identified using the tool starfish (Gluck-Thaler and Vogan 2023). Currently the most reliable identifying feature of Starships is a single ‘captain’ gene – a tyrosine recombinase gene containing a DUF3435 domain which is found in the first position of each Starship and directs the mobilisation of the element (Urquhart et al 2023b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All nine Gaeumannomyces strains were found to contain at least one giant TE belonging to the Starship superfamily of giant cargo-carrying TEs (Gluck-Thaler et al 2022), identified using the tool starfish (Gluck-Thaler and Vogan 2023). Currently the most reliable identifying feature of Starships is a single ‘captain’ gene – a tyrosine recombinase gene containing a DUF3435 domain which is found in the first position of each Starship and directs the mobilisation of the element (Urquhart et al 2023b).…”
Section: Resultsmentioning
confidence: 99%
“…These two genes were then used for a local blastp v2.13.0 search against all nine Gaeumannomyces assemblies reported here, which identified 33 full length hits (>95% identity) that were associated with insertions when visualised in Circos plots. This manual approach was then compared to Starship element identification using starfish v1.0 (Gluck-Thaler and Vogan 2023). One element identified by starfish was discounted as it consisted solely of a single predicted captain gene with no cargo or flanking repeats.…”
Section: Methodsmentioning
confidence: 99%